Integrated Soil Applied Fertilizers (Nitrogen, Zinc, and Boron) Effects on Growth and Yield of Sunflower (Journal of Agriculture and Veterinary Science, 2024)
In the case of sunflower production, precision agriculture can be used to determine the optimal fertilizer application rates and timings based on the specific soil and climatic conditions of a particular field. The response of sunflower to macro- and micronutrient applications has been observed. Field conditions were used to assess the effectiveness of applying nitrogen, zinc, and boron alone or in a mixture to improve the growth and production of sunflower HO-1. The experiment followed an RCBD design with a net plot size of 4x5 (20 m2). The study examined the impact of different applied soil fertilizers, including NPK. The suggested doses of T1 (control) and T2 (soil) of applied fertilizer Nitrogen 1000g ha-1, T3 soil applied fertilizer Zinc 1000g ha-1, T4 soil applied fertilizer Boron 1000g ha-1, T5 soil applied fertilizers Nitrogen 1000g ha-1 + Zinc 1000g ha-1; T6 Nitrogen 1000g ha-1 + Boron 1000g ha-1; T7 soil applied fertilizers Zinc 1000g ha-1 + Boron 1000g ha-1, T8 soil applied fertilizers Nitrogen 1000g ha-1 and boron 1000g ha-1, T8 were examined. The result indicated that the application of soil-applied fertilizers Nitrogen 1000g ha-1 zinc 1000g ha-1 and boron 1000g ha-1 in combination, yielded the most significant improvements in Maximum plant height: 181.0 cm; number of leaves per plant: 36.80; stem girth: 12.35; head diameter: 26.30; number of seeds: 652.0; seed weight: 40.74; seed index: 62.66; and seed yield (kg-1): 2230.